Why American Foreign Policy Fails Unsafe at Home and Despised Abroad - Jett, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book explores the recent changes in U.S. foreign policy, examines the roles that the six primary actors (the President, the Congress, the bureaucracy, non-governmental organizations, the media and the public) play in policy decisions, and assesses the potential for improvement within this system.